Water Spells: New Materialist Theoretical Insights from Animated Fantasy and Science Fiction - Vital, André Vasques (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
This essay analyses how water elementals in fantasy and science fiction animations created in the last decade suggest an aquatic materiality that raises alternative ways of thinking about a History of Waters. The analysis is conducted based on three characters from award-winning animations that embody, respectively, water in liquid, solid, and gaseous states: Lapis Lazuli (Steven Universe, 2013–2020), Elsa of Arendelle (Frozen 1, 2013 and Frozen 2, 2020), and Masami Yoshida (The Amazing World of Gumball, 2011–2019). The initial assumption is that animations in the fantasy and science fiction genres, in addition to being based on the historical circumstances of their time and even incorporating theories of history, allow the production of new possibilities of thinking historically. The three characters enable us to explore alternatives for a history that incorporates the contingent identity of waters that challenge certainties, permanence, and the traditional notion of historical agency while highlighting the evental and ambivalent nature of time.